An Improved Thermo‐TDR Technique for Monitoring Soil Thermal Properties, Water Content, Bulk Density, and Porosity. Issue 1 (22nd August 2019) - Peng, Wei; Lu, Yili; Xie, Xiaoting; Ren, Tusheng; Horton, Robert
Abstract : Core Ideas: A new thermo‐TDR sensor can determine soil thermal properties, water content, bulk density, porosity, and air‐filled porosity. The new theories are used to analyze the heat‐pulse data and TDR waveforms. The new sensor provides greater sensing volume and more accurate results than previous designs. The thermo‐time domain reflectometry (thermo‐TDR) technique is valuable for monitoring in situ soil water content (θ), thermal properties, bulk density (ρb ), porosity ( n ), and air‐filled porosity ( n a ) in the vadose zone. However, the previous thermo‐TDR sensor has several weaknesses, including limited precision of TDR waveforms due to the short probe length, small measurement volume, and thermal property estimation errors resulting from finite probe properties not accounted for by the heat pulse method. We have developed a new thermo‐TDR sensor design for monitoring θ, thermal properties, ρb, n, and n a . The new sensor has a robust heater probe (outer diameter of 2.38 mm and length of 70 mm) and a 10‐mm spacing between the heater and sensing probes, which provides a sensing volume three times larger than that of the previous sensor. The identical cylindrical perfect conductors and the tangent line–second‐order bounded mean oscillation theories were applied to analyze the raw data. Laboratory tests showed that θ values determined with the new sensor had a RMSE of 0.014 m 3 m −3 compared with 0.016 to 0.026 m 3 m −3 with the previous sensor. Soil thermal property estimates with the new sensor agreed well with modeled values. Soil ρb, n, and n a derived from θ and thermal properties were consistent with those derived from gravimetric measurements. Thus, the new thermo‐TDR sensor provides more accurate θ, thermal properties, ρb, n, and n a values than the previous sensor.